Durga Puja (Dashain) in Nepal: A Fusion of Ritual, Cultural, and Commercial Performance - Bhattarai, Achyutananda (Journal of Management, 2024)
This research article examines Durga puja (Dashain) in Nepal as a fusion of ritual, cultural, and commercial performances analyzing the impact of ritual and culture on commercial behaviors. Culture is largely concerned with the human values and beliefs that have been connected with the economic and commercial conduct of the people. The study explores how cultural performance shapes consumer behaviors besides strengthening social solidarity and preserving cultural identity. How the celebration of Durga Puja increases the financial activities of the country and what pros and cons it brings to society is analyzed. The qualitative data are collected from the relevant books, journal articles, and newspapers. Schechner’s “Theory of Ritual and Performance”, and Chattopadhyaya’s “From Religion to Culture” have been used as the theoretical framework. This research finds that the celebration of ritualistic cultural festivals preserves ritual and culture, strengthens social solidarity with identity, and increases commercial activities. It concludes that cultural festivals require celebrating in such a way that they can protect ritual and cultural identity, promote social solidarity, and progress commercial activities.